Should One Sell Domestic Firms to Foreign Ones? A Tale of Delegation, Acquisition and Collusion - Davide Dragone (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2008)
In a model of repeated Cournot competition under complete information, I show how the existence of a fringe of managerial firms affects the stability of a cartel of strict profit-maximizing firms. There always exists a critical dimension of the fringe that makes the cartel unstable, and this dimension is non-monotone in the total number of Örms. By appropriately selecting the dimension of the fringe, a policy maker can affect the equilibrium outcome. As an example, I consider the case of a domestic authority that is contemplating whether to allow entry of a fringe of managerial foreign firms in the domestic market to increase the competitive pressure, thereby enhancing domestic welfare.
Keywords: 330